2014
DOI: 10.1186/1756-0500-7-694
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of beta-lactamases in clinical isolates of Escherichia coli from Kathmandu, Nepal

Abstract: BackgroundThe trend of extended-spectrum beta-lactamases producing Escherichia coli (ESBL-EC) is increasing in Nepal. Limited studies have been reported investigating ESBL types and carbapenemases in E. coli.MethodsA cross sectional study was conducted between June 2012 to January 2013 in Kathmandu Medical College and Teaching Hospital, Nepal. Non-repetitive clinical samples from out-patient department (OPD) and Intensive Care Units (ICU) were processed for bacteriological culture and identification of E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
28
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 22 publications
14
28
6
Order By: Relevance
“…Other authors noted different observations in that clinical isolates of Escherichia coli and Pseudomonas aeruginosa carried bla CTX-M-types which was the most common (95.8%) followed by bla TEM (29.2%), bla SHV (7.3%), and bla VIM (12.5%) in Nepal [38]. These observations contribute to the knowledge of the epidemiology of VIM, TEM, SHV, and CTX-M-producing Gram-negative isolates that have now become endemic in major hospitals in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors noted different observations in that clinical isolates of Escherichia coli and Pseudomonas aeruginosa carried bla CTX-M-types which was the most common (95.8%) followed by bla TEM (29.2%), bla SHV (7.3%), and bla VIM (12.5%) in Nepal [38]. These observations contribute to the knowledge of the epidemiology of VIM, TEM, SHV, and CTX-M-producing Gram-negative isolates that have now become endemic in major hospitals in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Chander and Shrestha from nearby hospital reported the ESBL prevalence rate to be 13.5% [18] whereas, recently, Neupane et al have reported 33.2% of ESBL producers in their study [19]. Similarly, Ansari et al [20], Khanal et al [21], Pokhrel et al [10], Yadav et al [22], and Pant et al [23] have reported 24%, 25%, 25.8%, 26.8%, and 31.3% ESBL producers, respectively. These findings correlated well with those of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on prevalence, risk factors, and molecular characterization of ESBL producing organisms have been carried out from developed world but only few data are available concerning the genetic characterization of clinical isolates from Nepal [6, 9, 10]. Rapid and prompt detection of ESBL producing pathogenic Enterobacteriaceae is of utmost importance to promulgate the appropriate antimicrobial therapy and also for preventing cross-transmission to other patients in the vicinity [11].…”
Section: General Backgroundmentioning
confidence: 99%
“…CP-CRE prevalence rates are approximately 18% in two large hospitals in Nepal (99, 101). The most common carbapenemase in Enterobacteriaceae is NDM (101,102), with two new variants (NDM-8 and -12) described in Nepal recently (103,104). No mcr-positive Enterobacteriaceae have been found in Nepal to date.…”
Section: South Asiamentioning
confidence: 99%